2002
DOI: 10.1111/j.1553-2712.2002.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions in At-risk Emergency Department Patients

Abstract: ED outpatients in the at-risk group frequently present with pre-existing DIs. Medications initiated in the ED are a less frequent cause of DI in this group. Medication screening during an ED visit could complement the role of outpatient pharmacies and potentially improve ED patient safety. DIs are most frequently due to digoxin and warfarin in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 10 publications
1
15
1
1
Order By: Relevance
“…Each prescription had a median of 8 drugs (IQR 6-11). These frequencies were similar to those reported by other groups[2526]. Correlation coefficient between the number of drugs given to the patient and number of average potential adverse drug reactions found among the patients was 0.86.…”
supporting
confidence: 89%
“…Each prescription had a median of 8 drugs (IQR 6-11). These frequencies were similar to those reported by other groups[2526]. Correlation coefficient between the number of drugs given to the patient and number of average potential adverse drug reactions found among the patients was 0.86.…”
supporting
confidence: 89%
“…31,32 Our study adds to this information by demonstrating that the proportion of patients achieving clinically significant improvements due to hydrocodone is altered by the presence of drug-drug interactions. While previous studies have suggested that medications prescribed in the ED theoretically interact with the patients' regular medications, 33 our current study found that these interactions result in clinically significant changes in medication effectiveness. One interpretation of these data is that oxycodone should be preferred over hydrocodone due to more consistent clinical effects regardless of drug-drug interactions.…”
Section: Discussioncontrasting
confidence: 75%
“…One of the most commonly prescribed cardiac medications, digoxin interacts with numerous drugs, and these interactions often result in toxicity 17,18 . In a recent retrospective assessment of 200 emergency department outpatients at least 60 years old and taking multiple medications, more drug interactions were attributed to digoxin than any other medication 20 . Of the 86 drug interactions detected in these patients, 28 involved digoxin.…”
Section: Discussionmentioning
confidence: 99%